Dental caries and salivary Interleukin-6 among preterm postpartum women in relation to baby birth weight (Comparative study) - Tajer, Dhamiaa M; Al-Obaidi, Wesal A (Journal of Baghdad College of Dentistry, 2013)
Background: The physiologic, biochemical and anatomic changes that occur during pregnancy are extensive and may be systemic or local. However, most of these changes return to pre pregnancy status six weeks postpartum. The aim of the study was to investigate the effect of dental caries among preterm postpartum women and it’s relation to baby birth weight and salivary interleukin-6 (IL-6). Materials and methods: 66 postpartum women were examined, 33 preterm postpartum women (study group) and 33 full term postpartum women (control group). Dental caries was recorded using, decayed, missing and filled surfaces index, also assess the decayed lesion by severity. Salivary samples were taken from all subjects to estimate salivary IL-6 levels. Babies’ birth weight also was measured. Results: Data of the present study showed a higher caries severity among study group compared to control group, with no statistically significant difference (P> 0.05). For both groups, the initial decayed surface D¬2 was the lightest value for both groups. While the deep frank cavitations D4 was the lowest in study group with no data recording among control group. The result revealed highly significant difference in baby birth weight between the two groups. The correlation between DS and salivary IL-6 was highly significant, and a significant correlation noticed between D3 and salivary IL-6 in study group. In control group, a highly significant positive correlation was detected between baby birth weight and DMFS, and a significant correlation was obscured between baby birth weight with decayed surface, also a significant correlation was found between salivary IL-6 and decayed surface in the same group. Conclusion: During pregnancy, a woman may be particularly amenable to disease prevention and health promotion interventions that could enhance her oral health on that of her infant’s, due to the potential associations between oral health and preterm delivery and baby birth weight.